(untitled) (Research, Society and Development, 2023)
To cross-culturally adapt the Oral Mucositis Quality of Life (OMQoL) instrument to Brazilian Portuguese and assess its psychometric properties. The cross-cultural adaptation was performed in six steps. In one of them, the instrument was applied to 40 participants who indicated whether items were comprehensible, which helped elaborate the final version. In the validation phase, 102 participants were interviewed. The sample included patients undergoing oncologic treatment. The softwares R version 4.0.5 and the R Studio 1.4.1717 were used, and the initial database used Dplyr, Tidyr, Gplot2. To assess the psychometric properties, confirmatory factor analysis was performed. The dimensionality of the instrument was investigated using a network analysis approach. The wording of items in a couple of questions were revised after participants indicated a lack of clarity. The relationship between the degree of oral mucositis and the different hospital groups showed statistically significant differences (p<0.001). Confirmatory factor analysis resulted in good index scores (RMSEA=0.08; CFI=0.91; TFI=0.89; CD=0.99), which showed that the instrument had good properties. The OMQoL was translated, adapted and its Brazilian version adequately reflected the original instrument. The OMQoL is valid for the Brazilian population, as well as its short form proposed by this study.